Outcomes with various drug eluting or bare metal stents in patients with diabetes mellitus: mixed treatment comparison analysis of 22 844 patient years of follow-up from randomised trials. (10th August 2012) - Bangalore, Sripal; Kumar, Sunil; Fusaro, Mario; Amoroso, Nicholas; Kirtane, Ajay J; Byrne, Robert A; Williams, David O; Slater, James; Cutlip, Donald E; Feit, Frederick
Abstract : Objectives To evaluate the efficacy and safety of currently used drug eluting stents compared with each other and compared with bare metal stents in patients with diabetes. Design Mixed treatment comparison meta-analysis. Data sources and study selection PubMed, Embase, and CENTRAL were searched for randomised clinical trials, until April 2012, of four durable polymer drug eluting stents (sirolimus eluting stents, paclitaxel eluting stents, everolimus eluting stents, and zotarolimus eluting stents) compared with each other or with bare metal stents for the treatment of de novo coronary lesions and enrolling at least 50 patients with diabetes. Primary outcomes Efficacy (target vessel revascularisation) and safety (death, myocardial infarction, stent thrombosis). Results From 42 trials with 22 844 patient years of follow-up, when compared with bare metal stents (reference rate ratio 1) all of the currently used drug eluting stents were associated with a significant reduction in target vessel revascularisation (37% to 69%), though the efficacy varied with the type of stent (everolimus eluting stents∼sirolimus eluting stents>paclitaxel eluting stents∼zotarolimus eluting stent>bare metal stents). There was about an 87% probability that everolimus eluting stents were the most efficacious compared with all others, though there were limited usable data for the zotarolimus eluting Resolute stent in patients with diabetes. Moreover, there was no increased risk of any safety outcome (including very late stent thrombosis) with any drug eluting stents compared with bare metal stents. There was about a 62% probability that the everolimus eluting stent was the safest stent for the outcome of "any" stent thrombosis. Conclusions Among patients with diabetes treated with coronary stents all currently available drug eluting stents were efficacious without compromising safety compared with bare metal stents. There were relative differences among the drug eluting stents, such that the everolimus eluting stent was the most efficacious and safe.